Measuring The Effectiveess of Consumer Dispute Resolution on Small Value E-Commerce Transaction - Mosgan Situmorang (Law and Human Rights Policy Strategy Agency, Ministry of Law and Human Rights of The Repub, 2022)
The development of very advanced information technology has changed the pattern of trade carried out by the community. Buying and selling are no longer only carried out directly with the meeting of sellers and buyers in certain places, but can be performed from anywhere with the help of information technology. E-commerce or trade conducted online is growing very rapidly from day to day and has become a lifestyle for people, especially in urban areas. In addition to having a positive impact, e-commerce also has a negative impact, because the laws governing it have not developed as fast as these trading practices. One of the problems is related to the existing settlement institutions. Existing institutions are seen as not being able to properly accommodate consumer disputes that arise. The dispute resolution available is considered conventional and has not accommodated disputes that arise, especially for claims of small value, which make up the majority of the online trading section. In connection with the above description, a research was conducted. The question in this study is how effective is the dispute resolution agency currently available, especially for e-commerce disputes of small value. This research was conducted with a normative juridical method. From the results of the study it can be concluded that the existing dispute resolution institutions cannot be said to be effective, especially in consumer disputes of small value, adequate dispute resolution for claims of small value arising from online buying and selling. From the results of the research, recommendations are given to form existing dispute resolution institutions, especially BPSK, to increase their role and capacity so that they can accommodate small-value disputes quickly and at low cost